2009
DOI: 10.1002/ange.200804734
|View full text |Cite
|
Sign up to set email alerts
|

Semisynthese eines homogenen Glycoprotein‐Enzyms: Ribonuclease C (Teil 1)

Abstract: Sieben auf einen Streich: Durch die effiziente Bildung von gemischten Disulfiden an dem thiolreichen Fusionsprotein A konnte nach Inteinabspaltung das Cys‐Fragment B mit sieben oxidationsgeschützten Cysteinen erhalten werden. Die native chemische Ligation von B mit synthetischen Glycopeptidthioestern ergibt Glycoproteine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 54 publications
0
4
0
1
Order By: Relevance
“…[11,12] The currently used methodology for the synthesis of N-glycoproteins comprises solid-phase glycopeptide synthesis, [13,14] the use of transglycosidases [15] or enzymatic remodeling, [16] the use of engineered cell lines, [17,18] and in particular the application of chemoselective ligation methods. [19][20][21] In the preceding Communication [22] we demonstrated that active RNase A can be obtained by expressed chemical ligation using a recombinant RNase segment that was chemically stabilized by transformation of its seven cysteines into mixed disulfides. We have taken this approach further to the synthesis of a single glycoform of bovine RNase carrying a biantennary complextype nonasaccharide (RNase C [23] ) by sequential [21,24] native chemical ligations (Scheme 1).…”
mentioning
confidence: 97%
“…[11,12] The currently used methodology for the synthesis of N-glycoproteins comprises solid-phase glycopeptide synthesis, [13,14] the use of transglycosidases [15] or enzymatic remodeling, [16] the use of engineered cell lines, [17,18] and in particular the application of chemoselective ligation methods. [19][20][21] In the preceding Communication [22] we demonstrated that active RNase A can be obtained by expressed chemical ligation using a recombinant RNase segment that was chemically stabilized by transformation of its seven cysteines into mixed disulfides. We have taken this approach further to the synthesis of a single glycoform of bovine RNase carrying a biantennary complextype nonasaccharide (RNase C [23] ) by sequential [21,24] native chemical ligations (Scheme 1).…”
mentioning
confidence: 97%
“…Related research shows that R. ferrugineus is rich in phospholipids (2.6-9.3 g/100 g lipid) (Khanittha, Manat & Worawan, 2020). Moreover, the average protein content of edible insects is 10%-25% of fresh weight or 35%-60% of dry weight (Melo et al, 2011;Schlüter et al, 2016), even higher than the protein content of grains, lentils and soybeans (Bukkens, 1997). In fact, the dietary protein derived from insects is close to 50%, which is more market value than other proteins (Dobermann, Swift & Field, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…[23] In a recent issue of Angewandte Chemie, two back-to-back papers by the Unverzagt group described progress in a powerful synthesis of a single glycoform of an enzyme. [40,41] They chose an excellent model system with which to demonstrate these strategic principles. Ribonuclease (RNase) is a 124-residue protein that has been an archetype of glycoprotein function by virtue of its single N-glycosylation site at Asn34.…”
mentioning
confidence: 99%